The Regression Models of Impact Strength of Coir Coconut Fiber Reinforced Resin Matrix Composite Materials - Muhamad Fitri; Shahruddin Mahzan (Institute for Research on Innovation and Industrial System (IRIS), 2020)
The need of coconuts in Indonesia is relatively high. The use of large quantities of coconuts produces large amounts of organic waste from coco fiber, which tends to become waste if it is not used to be beneficial for humans.One of the potential uses of coconut fiber is as a reinforcement of natural fibers in polymer matrix composite materials. Recently, the applications of composite materials have been expanded widely including structural angine component which whitstand certain load like impact load. But most of them used synthetic fiber. Although the use of natural fibers as reinforcement in composite materials has been widely studied, their use is still limited because natural fibers have their own advantages and disadvantages. The purpose of this study was to measure the impact strength of specimens of coconut fiber reinforced polymer matrix composite material, and to determine the effect of the length and concentration of coconut fiber on its impact strength. A significant and valid regression model was also generated in this research, that states the relationship between fiber length and fiber content of resin matrix composite material to its impact strength. The result shows that the impact strength of the samples were influenced by fiber content and fiber length. The regression models for the impact strength of resin composite reinforced with coconut fiber is Y = 4.44 +0.180 X1 – 0.52 X2 Where: Y = Impact Strength (kJ/m2), and X1= Fiber length (mm), and X2= Fiber content (%).